2019
DOI: 10.1002/anie.201913895
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Hydride Reduction of Polycyclic Aromatic Hydrocarbons

Abstract: A molecular calcium hydride effects the two electron reduction of polyaromatic hydrocarbons, including naphthalene (E0=−3.1 V).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 55 publications
2
25
0
Order By: Relevance
“…Although an exchange spectroscopy (EXSY) NMR experiment demonstrated that 2 and 2’ are in equilibrium at room temperature, attempts to quantify this process by variable temperature 1 H NMR studies were frustrated by the competitive redistribution to the homoleptic ytterbium complex, [(BDI Dipp ) 2 Yb] 36 , and facile Yb–H/D exchange with the deuterobenzene solvent. In this latter regard, the signal associated with the hydride ligand of 2 was observed to decrease if left in benzene- d 6 for extended periods of time (>6 h), concomitant with the formation of a new signal in the 2 H NMR spectrum centred at 7.92 ppm, which was assigned as the ytterbium deuteride [BDI Dipp YbD] 2 , 2- d 7 , 37 .…”
Section: Resultsmentioning
confidence: 99%
“…Although an exchange spectroscopy (EXSY) NMR experiment demonstrated that 2 and 2’ are in equilibrium at room temperature, attempts to quantify this process by variable temperature 1 H NMR studies were frustrated by the competitive redistribution to the homoleptic ytterbium complex, [(BDI Dipp ) 2 Yb] 36 , and facile Yb–H/D exchange with the deuterobenzene solvent. In this latter regard, the signal associated with the hydride ligand of 2 was observed to decrease if left in benzene- d 6 for extended periods of time (>6 h), concomitant with the formation of a new signal in the 2 H NMR spectrum centred at 7.92 ppm, which was assigned as the ytterbium deuteride [BDI Dipp YbD] 2 , 2- d 7 , 37 .…”
Section: Resultsmentioning
confidence: 99%
“…In a third set of calculations the pathway for benzene hydrogenation with the most active (TRIP) 2 NBaH catalyst has been evaluated (Scheme b). The cycle starts with benzene complexation followed by formation of a Meisenheimer anion which is surprisingly exothermic (Ar3: −3.5 kcal mol −1 ); breaking benzene's aromaticity by formation of the Meisenheimer anion is generally endothermic . Two possible transition states for the reaction with H 2 have been located (Ar5* and Ar6*).…”
Section: Resultsmentioning
confidence: 99%
“…Thec ycle starts with benzene complexation followed by formation of aM eisenheimer anion which is surprisingly exothermic (Ar3: À3.5 kcal mol À1 ); breaking benzenesa romaticity by formation of the Meisenheimer anion is generally endothermic. [5,29,49] Tw opossible transition states for the reaction with H 2 have been located (Ar5* and Ar6*). Thet ransition state for formation of 1,3-cyclohexadiene (Ar5*) is 1.6 kcal mol À1 lower in energy than that for 1,4-cyclohexadiene formation (A6*).…”
Section: Methodsmentioning
confidence: 98%
“…[27] Stock demonstrated that LiN(iPr) 2 or KN(SiMe 3 ) 2 catalyze the reduction of activated PA H 'sl ike anthracene or naphthalene under drastic conditions (25 mol %c atalyst, 200 8 8C, 70 bar H 2 , 18 h). [28] TheH ill group very recently demonstrated the stoichiometric reduction of activated PA H'sw ith Ca hydride complex IV [29] but the catalytic hydrogenation of aromatic rings with Ae metal catalysts has hitherto not been reported.…”
Section: Introductionmentioning
confidence: 99%